Life - As a Matter of Fat The Emerging Science of Lipidomics - Mouritsen, Ole G. (The Frontiers Collection,, 2005)
LIFE - as a Matter of Fat Lipidomics is the science of the fats called lipids. Lipids are as important for life as proteins, sugars, and genes. The present book gives a multi-disciplinary perspective on the physics of life and the particular role played by lipids and the lipid-bilayer component of cell membranes. The book is aimed at undergraduate students and young research workers within physics, chemistry, biochemistry, molecular biology, nutrition, as well as pharmaceutical and biomedical sciences. The emphasis is on the physical properties of lipid membranes seen as soft and molecularly structured interfaces. By combining and synthesizing insights obtained from a variety of recent studies, an attempt is made to clarify what membrane structure is and how it can be quantitatively described. Furthermore, it is shown how biological function mediated by membranes is controlled by lipid membrane structure and organization on length scales ranging from the size of the individual molecule, across molecular assemblies of proteins and lipid domains in the range of nanometers, to the size of whole cells. Applications of lipids in nano-technology and biomedicine are also described. The Emerging Science of Lipidomics We have just witnessed a scientific revolution at the end of the 20th century that took us through the genomics era with a focus on sequencing genes and mapping gene products. We are now in the middle of the proteomics era where the multitude of proteins that are encoded in the genes are identified and their functions are unveiled. In front of us we have a new era recognizing the role of lipids. The science of lipidomics is emerging. Lipidomics involves a quantitative experimental and theoretical study of, e.g. lipid and membrane self-assembly, lipid-protein interactions, lipid-gene interactions, and the biophysical properties of lipid structure, function, and dynamics. .